Ketimpangan Pendapatan dan Determinan PDRB Per Kapita Kabupaten/Kota di Pulau Sulawesi Tahun 2017-2020 - Azzahra Zauza Inniswa Rahmadhana; Agung Priyo Utomo (Seminar Nasional Official Statistics, 2022)
Income inequality is a crucial problem which is common in developing countries. Sulawesi is known to have various conditions of inequality between regions. The high variations of inequality in Sulawesi is the basis for importance of this research which aims to examine the general description of regional income inequality and per capita GRDP of districts/cities in Sulawesi for the 2017-2020 period, also examine the determinant of per capita GRDP in Sulawesi regions, taking into account spatial heterogeneity. Empirical results shows that there is spatial heterogeneity of per capita GRDP in 81 regions in Sulawesi. Using Geographically Weighted Panel Regression with Kernel Adaptive Exponential and 95% level of winsorize, average length of school and labor productivity significantly increase per capita GRDP in 80 and 54 regions, respectively. Open Unemployment Rate significantly decrease per capita GRDP in 40 regions, while population growth significantly decrease per capita GRDP in 37 regions.